VALUASI EKONOMI EKOSISTEM TERUMBU KARANG PULAU WARBAL DI KAWASAN KONSERVASI KEI KECIL KABUPATEN MALUKU TENGGARA - Mahakena, Mentari A; Siahainenia, Stevanus M; Sahetapy, Dicky (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2021)
Economic valuation plays an important role as a comprehensive instrument to assess prices (price tags) on the existence of goods and services of an ecosystem. This research aims to analyze utilization conditions including utilization value, non-utilization value and total economic value of coral reef resources and formulate a strategy for managing the reef ecosystem of Warbal Island and surrounding waters. The research on the economic valuation of warbal island coral reef ecosystem and surrounding waters was conducted in July-November 2019. Primary data collection was done through field observations and interviews, while secondary data was obtained through references from the Village Government, Southeast Maluku Fisheries Service, WWF Indonesia and scientific publications. Data was analyzed using methods of analysis of total economic value from use valueand non-use value. Based on the results of the study obtained the total economic value of the utilization and non-utilization of coral reef resources in Warbal Island and surrounding waters reached IDR. 7.275.603.819/year. The value of utilization of coral reef resources of Warbal Island and surrounding waters amounted to IDR. 7.257.318.819/year, while the non-utilization value of coral reef resources amounted to IDR. 18.250.000/year. At least, there are 11 strategies and 22 management directives recommended for the management of Warbal Island coral reef resources and surrounding waters. ABSTRAK Valuasi ekonomi berperan penting sebagai instrument yang komperhensif untuk memberi penilaian harga (price tag) terhadap keberadaan barang dan jasa suatu ekosistem. Penelitian ini bertujuan untuk menganalisisnilai pemanfaatan, nilai non pemanfaatan dan nilai ekonomi total sumberdaya terumbu karang serta merumuskan strategi pengelolaan ekosistem terumbu kawasan Pulau Warbal dan perairan sekitarnya. Penelitian tentang valuasi ekonomi ekosistem terumbu karang Pulau Warbal dan perairan sekitarnya dilakukan pada Juli-Nopember 2019. Pengumpulan data primer dilakukan melalui pengamatan lapangan dan wawancara, sedangkan data sekunder diperoleh melalui referensi dari Pemerintah Desa, Dinas Perikanan Maluku Tenggara, WWF Indonesia dan publikasi ilmiah. Data dianalisis menggunakan metode analisis nilai ekonomi total dari use value dan non use value. Berdasarkan hasil penelitian diperoleh nilai ekonomi total dari pemanfaatan dan non pemanfaatan sumberdaya terumbu karang kawasan Pulau Warbal dan perairan sekitarnya mencapai Rp. 7.275.603.819/tahun. Nilai pemanfaatan sumberdaya terumbu karang Pulau Warbal dan perairan di sekitarnya sebesar Rp. 7.257.318.819/tahun, sedangkan nilai non pemanfaatan sumberdaya terumbu karang sebesar Rp. 18.250.000/tahun. Terdapat 11 strategi dan 22 arahan pengelolaan yang direkomendasikan untuk pengelolaan sumberdaya terumbu karang Pulau Warbal dan perairan di sekitarnya. Kata kunci: valuasi ekonomi, ekonomi total, nilai pemanfaatan, terumbu karang, Maluku Tenggara